Formation of nascent char structure during the fast pyrolysis of mallee wood and low-rank coals - Zhang, L.; Li, T.; Quyn, D.; Dong, Li; Qiu, P.; Li, Chun-Zhu (Elsevier Ltd, 2015)
The structural evolution of nascent chars during the fast pyrolysis of a wood and two low-rank coals was investigated in this study. Western Australian Collie sub-bituminous coal, Victorian Loy Yang brown coal and Western Australian mallee wood were pyrolysed in a wire-mesh reactor that is capable of providing rapid heating rates (up to 5000 K s−1) and accurate holding time (in increments of 10 ms) at peak temperature. FT-Raman spectroscopy was used to characterise the key structural features of raw fuels and nascent chars. The combined use of a wire-mesh reactor and a FT-Raman spectroscopy has given insights into the structural transformation from coal/biomass to nascent chars. There were insignificant changes in the aromatic ring systems of two coals during the initial fast heating from room temperature to 600 °C. During holding at 600 °C, the changes that occurred in ring systems for the three fuels were different. Mallee wood and Loy Yang coal underwent more changes than Collie coal. In addition, mallee wood had ring condensation during holding at 600 °C up to 30s. However, little growth in large aromatic rings of two coals was observed during holding at 600 °C up to 50 s.